Pernyataan Kontroversial Pejabat Negara Dalam Pemberitaan Media (Analisis Framing pada Detik.com dan Kompas.com) - Chandra Agustin, Dinar Ayu; Danang Trijayanto; Ela Indah Dwi Syayekti (Kediri Journal of Journalism and Digital Media (KJOURDIA), 2025)
This research aims to analyze and compare the media framing of the Indonesian Minister of Finance's controversial statements regarding the "17+8" demands, which triggered a political communication crisis. Utilizing a qualitative approach with the Robert N. Entman framing analysis model, the study compares nine news articles from the online portals Kompas.com (4 articles) and Detik.com (5 articles) published between September 9 and 10, 2025. The results indicate that both media effectively served a function of social control by maintaining a consensus on demanding moral accountability from the official. However, a significant difference in problem diagnosis was found: Kompas.com framed the issue as systemic, criticizing the political elite's mentality of dismissing public demands, whereas Detik.com focused on the personal dimension, highlighting the official's failure in adapting his communication ethics. This contrast leads to a main conclusion: that state officials are required to possess not only substantive competence and professional ability, but must also be equipped with deep empathy and behavioral accountability in all public communication. The result of this study contribute to strengthening research in the fields of political communication and media framing analysis, particularly by highlighting how media discourse construction shapes public perception of communication crises involving state afficials.